Climate Vulnerability Assessment : Making Fiji Climate Resilient - Government of Fiji (World Bank, Washington, DC, 2017)
The country has an area of 18,000 km spread over 332 islands, of which about 110 are inhabited. Most of the population lives on two large islands, Viti Levu and Vanua Levu. Fiji faces significant development challenges, and the government has set ambitious development objectives to address them. Economic growth in Fiji has been relatively slow in the last decades. Recently, the 20-year and 5-year National Development Plan was prepared to respond to this situation; its ambitious objectives are to more than double the real gross domestic product (GDP) per capita by 2036 and to provide universal access to all services, including housing, electricity, clean and safe water and sanitation, high-quality education, and health care.